Selective nerve root injection of ozone for the treatment of phantom limb pain: Three case reports. Issue 16 (April 2020) - Li, Juanhong; Li, Tianzuo; Li, Guiying; Liu, Hongfu; Zhang, Xiaogai
Abstract: Rationale: Phantom limb pain (PLP) refers to a common complication following amputation, which is characterized by intractable pain in the absent limb, phantom limb sensation, and stump pain. The definitive pathogenesis of PLP has not been fully understood, and the treatment of PLP is still a great challenge. Till now, ozone injection has never been reported for the treatment of PLP. Patient concerns: We report 3 cases: a 68-year-old man, a 48-year-old woman, and a 46-year-old man. All of them had an amputation history and presented with stump pain, phantom limb sensation, and sharp pain in the phantom limb. Oral analgesics and local blocking in stump provided no benefits. Diagnosis: They were diagnosed with PLP. Interventions: We performed selective nerve root ozone injection combined with ozone injection in the stump tenderness points. Outcomes: There were no adverse effects. Postoperative, PLP, and stump pain were significantly improved. During the follow-up period, the pain was well controlled. Lessons: Selective nerve root injection of ozone is safe and the outcomes were favorable. Ozone injection may be a new promising approach for treating PLP.